2018
DOI: 10.4103/ijpc.ijpc_63_18
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles and life satisfaction in palliative care

Abstract: Background:Patients in palliative care suffer variously due to underassessment of needs and suboptimal intervention, coupled with lack of access to palliative care. This study attempts to identify effective coping strategies which lead to life satisfaction, among those afflicted with terminal cancer.Materials and Methods:This observational, cross-sectional study was carried out among terminally-ill cancer patients undergoing palliative care. Cancer patients receiving palliative care who give consent and were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…In the current study, female older adults had higher levels of religious coping than male older adults. This finding is consistent with previous studies, in which female seniors reported higher levels of religiousness than did male seniors (Garg Chauhan and Sabreen 2018 ; Handal and Lace 2017 ; Henrie and Patrick 2014 ). This finding is also consistent with terror management theory (TMT), which states that being male is positively associated with religious doubt and negatively associated with religiousness (Henrie and Patrick 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, female older adults had higher levels of religious coping than male older adults. This finding is consistent with previous studies, in which female seniors reported higher levels of religiousness than did male seniors (Garg Chauhan and Sabreen 2018 ; Handal and Lace 2017 ; Henrie and Patrick 2014 ). This finding is also consistent with terror management theory (TMT), which states that being male is positively associated with religious doubt and negatively associated with religiousness (Henrie and Patrick 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…PFC helps them overcome their distress because it involves active efforts to manage stressful situations and eliminate them by modifying individual behaviors. PFC was found to be more effective than other methods in coping with patients' depressive and anxious behaviors (Garg et al, 2018). PFC strategies include being realistic, indulgent, and supportive and learning from others, which enable participants to regain a sense of wellbeing after an emotional challenge (Walshe et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on patients with rheumatoid arthritis, it was found that life satisfaction increases by promoting resilience and implementing emotion-oriented coping strategies (36). In patients who received palliative care, the use of spiritual adjustment and emotion-oriented coping strategies, especially in female patients, led to an improved quality of life (37), and as a result, life satisfaction. Promoting coping and adjustment, by making positive changes in patients' mood, leads to the improvement of health-related quality of life in them (38,39), which in turn, results in greater satisfaction with the existing conditions.…”
Section: Discussionmentioning
confidence: 99%